Antihyperlipidemic potential of herbals - Yadav, Swati; Satapathy, Tilochan; Roy, Amit; Prasad, Pushpa (Journal of Applied Pharmaceutical Research, 2014)
One of the most widespread diseases in the world is Coronary Heart Disease (CHD). It is also one of the most preventable. This review explores the management of CHD through changes in dietary modifications, lifestyle, and the use of dietary supplements and botanicals.